2021
DOI: 10.1002/dac.4749
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain‐based patient centric health care communication system

Abstract: Summary The rapid increase in health care data breaches with the existing centralized systems emphasizes a decentralized health care system while ensuring reliability, privacy, security, and trust. Further, to ensure trust in the medical community, scientist, and pharmaceutical, it is essential to improve the quality of health care data management. In this direction, we proposed a blockchain‐based decentralized privacy‐preserving EMR management (DPEM), which can ensure accountability and integrity. We propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…[18] proposed a flexible Pedersen commitment implementation based on elliptic curves in twisted Edwards form, which helped to improve security, adaptive data size, and data point flexibility. [19] investigated optimal prime fields for lightweight ECC implementation, focusing on performance and security. [20] performed a comparative study of algorithms for batch verification of Edwards curve digital signatures and showed that small batch size algorithms S2' and SP yield better speedup results than the default algorithm N'.…”
Section: Digital Signaturementioning
confidence: 99%
See 2 more Smart Citations
“…[18] proposed a flexible Pedersen commitment implementation based on elliptic curves in twisted Edwards form, which helped to improve security, adaptive data size, and data point flexibility. [19] investigated optimal prime fields for lightweight ECC implementation, focusing on performance and security. [20] performed a comparative study of algorithms for batch verification of Edwards curve digital signatures and showed that small batch size algorithms S2' and SP yield better speedup results than the default algorithm N'.…”
Section: Digital Signaturementioning
confidence: 99%
“…[76] enhanced Edwards curve to achieve nonrepudiation in IoT blockchain ecosystem. [19] Their work demonstrates the use of the Edwards curve and showcases how they can reduce implementation space, and operational cost and perform fast verification.…”
Section: Edwards Curve Application In Iotmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the blockchain network is not centralized. [1][2][3] The concept that guarantees data integrity and immutability in the blockchain is a computational process named mining. A miner performs an intensive computing process to add a new block to the existing blockchain.…”
Section: Introductionmentioning
confidence: 99%
“…The transactions added to the blockchain network cannot be modified or deleted. Therefore, the blockchain network is not centralized 1–3 …”
Section: Introductionmentioning
confidence: 99%